Analysis of Victim Cases Dental Technician in Health Law in Indonesia - Dara Chyntia Dewi (Journal of Social Science, 2021)
There are so many victims of dental technicians in Indonesia that require special attention. The factor causing many victims is the number of dental technicians who are illegal and have exceeded the limit of authority that dentists should do. In fact, the authority of a dental technician is only limited to making and installing removable dentures, but the fact is that many dental technicians abuse the rules. This caused many victims from minor illness to death. This is certainly not in accordance with what is stated in the health law in Indonesia. The government must be strict in enforcing applicable health laws regarding dental technicians.